2017
DOI: 10.1080/03079457.2017.1393044
|View full text |Cite
|
Sign up to set email alerts
|

Propagation and titration of infectious bursal disease virus, including non-cell-culture-adapted strains, usingex vivo-stimulated chicken bursal cells

Abstract: Infectious bursal disease virus (IBDV) is a Birnaviridae family member of economic importance for poultry. This virus infects and destroys developing B lymphocytes in the cloacal bursa, resulting in a potentially fatal or immunosuppressive disease in chickens. Naturally occurring viruses and many vaccine strains are not able to grow in in vitro systems without prior adaptation, which often affects viral properties such as virulence. Primary bursal cells, which are the main target cells of lymphotropic IBDV in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 45 publications
1
27
1
Order By: Relevance
“…Our work complements that of S ebastien Soubies et al in the lab of Nicolas Eterradossi, who have recently demonstrated that phorbol 12-myristate 13-acetate (PMA)-stimulated B cells can also support IBDV replication [40]. Ex vivo models of IBDV infection allow virus-host cell interactions to be studied in the relevant host cells, retaining the advantages of in vivo studies without the limitations of multiple cell types that might confound the data.…”
Section: Discussionsupporting
confidence: 57%
“…Our work complements that of S ebastien Soubies et al in the lab of Nicolas Eterradossi, who have recently demonstrated that phorbol 12-myristate 13-acetate (PMA)-stimulated B cells can also support IBDV replication [40]. Ex vivo models of IBDV infection allow virus-host cell interactions to be studied in the relevant host cells, retaining the advantages of in vivo studies without the limitations of multiple cell types that might confound the data.…”
Section: Discussionsupporting
confidence: 57%
“…In addition, it is important to isolate the primary cells as soon as possible after the organ harvest to limit cell death. The need to use chCD40L is a limitation of the technique; however, work conducted by Soubies et al shows that the use of phorbol 12-myristate 13-acetate (PMA) to prolong bursal cell viability instead of chCD40L 14 may enable the model to be adopted by a greater number of laboratories. The protocol outlined above determines the optimal concentration of chCD40L empirically, by culturing primary B cells in serially diluted concentrations of the molecule and observing cell proliferation and viability.…”
Section: Discussionmentioning
confidence: 99%
“…Following identification of the gene encoding chicken CD40L (chCD40L), a soluble fusion protein was engineered that, when added to the culture media, induced the proliferation of chicken primary B cells ex vivo 12 . In 2015, B cells cultured in this fashion were found to support the replication of MDV 2 and in 2017, we and others found that primary bursal cells stimulated with chCD40L could be used as a model to study IBDV replication 13 14 . Here, we describe the isolation and culture of chicken primary bursal cells, the infection of the cells with IBDV, and the quantification of viral replication.…”
Section: Introductionmentioning
confidence: 90%
“…The reason for the buffer overflow is that the parameters entered by the user are not carefully checked in the program. For example, it is as the following program [15]: void function(char *str) { char buffe r [16]; strcpy(buffer,str); } The strcpy () above will directly transform the content from str to copy into the buffer. So long as the length of str is greater than 16, it will cause buffer overflow and cause the program to run wrong.…”
Section: Analysis Of Computer Network Attackmentioning
confidence: 99%
“…The most common way is to create a buffer overflow to enable the program to run a user shell and execute other commands through shell. If the program belongs to root and has suid permissions, the attacker gets a shell with root permissions and can operate any on the system [16].…”
Section: Analysis Of Computer Network Attackmentioning
confidence: 99%